2002
DOI: 10.1590/s1516-35982002000400017
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento ponderal e testicular, concentrações periféricas de testosterona e características de abate em touros da raça Nelore

Abstract: RESUMO -Um experimento foi conduzido com o objetivo de avaliar o desenvolvimento ponderal e testicular, as concentrações periféricas de testosterona (T) e características de abate, dos 10 aos 30 meses de idade, em tourinhos da raça Nelore (n=27). Entre 11 e 21 meses, os animais foram tratados com GnRH e amostras de sangue, coletadas 0, 1,5 e 3,0 horas depois. Aos 30 meses, os animais foram abatidos. O peso vivo (PV) dos animais variou de 195,2 ± 3,8 kg a 439,1 ± 8,1 kg entre 10 e 30 meses e o rendimento de car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
14
4
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 16 publications
7
14
4
7
Order By: Relevance
“…According to studies conducted in the Bos taurus and Bos indicus, puberty coincides with the typical peak in basal concentrations of testosterone in the peripheral circulation (AMANN, 1983;ARAVINDAKSHAN et al, 2000;GHOLAMI et al, 2010;ERICKSON, 2011). For the Nelore bulls used in the present study, the characteristic peak in basal testosterone occurred at 18 mo., suggesting these animals reached puberty at that age, as we have originally pointed out (MOURA; RODRIGUES; MARTINS FILHO, 2002). Previous reports have shown that Nelore bulls attain puberty at ages from 14.8 to 22.1 mo.…”
Section: Resultssupporting
confidence: 74%
See 4 more Smart Citations
“…According to studies conducted in the Bos taurus and Bos indicus, puberty coincides with the typical peak in basal concentrations of testosterone in the peripheral circulation (AMANN, 1983;ARAVINDAKSHAN et al, 2000;GHOLAMI et al, 2010;ERICKSON, 2011). For the Nelore bulls used in the present study, the characteristic peak in basal testosterone occurred at 18 mo., suggesting these animals reached puberty at that age, as we have originally pointed out (MOURA; RODRIGUES; MARTINS FILHO, 2002). Previous reports have shown that Nelore bulls attain puberty at ages from 14.8 to 22.1 mo.…”
Section: Resultssupporting
confidence: 74%
“…Results about age-related changes in scrotal circumference and basal and GnRH-stimulated testosterone have been previously described in detail (MOURA; RODRIGUES; MARTINS FILHO, 2002). In summary, scrotal circumference of the Nelore bulls increased between 10 and 30 mo.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations